Highly flexible polymer-carbon dot-ferric ion nanocomposite hydrogels displaying super stretchability, ultrahigh toughness, good self-recovery and shape memory performance. (October 2017) - Hu, Yang; Li, Yaozong; Wang, Di; Zhou, Wuyi; Dong, Xianming; Zhou, Shiyao; Wang, Chaoyang; Yang, Zhuohong
Graphical abstract: Highlights: The polymer-carbon dot-ferric ion hydrogels (CF-hydrogels) were synthesized. CF-hydrogels were dual crosslinked by carbon dots and Fe 3+ ions as cross-linkers. The optimal CF hydrogel showed very balanced and high mechanical properties. CF hydrogel had good self-recovery, fatigue resistance and shape memory ability. Abstract: The super stretchability, ultrahigh toughness, good self-recovery and shape memory performance are very important for the practical application of hydrogels. However, most of hydrogels do not demonstrate the above-mentioned features at the same time. In this study, we develop a promising and versatile strategy for the synthesis of novel tough poly(acrylamide-co-acrylic acid)-carbon dot-ferric ion (PAmAc-Cdot -Fe 3+ ) nanocomposite (NC) hydrogel with a dual cross-linked network, which is triggered by carbon dots (C-dots) and Fe 3+ ions as physical cross-linkers. The introduction of Fe 3+ ions into the first C-dot cross-linked hydrogel can form strong coordinate bonds with COO − groups of PAmAc chains and C-dots, and obviously increase the mechanical properties of hydrogels. Varying C-dot content, Ac content, or immersing time in FeCl3 solution can facilely adjust the mechanical properties of hydrogels. At optimal conditions, the PAmAc-Cdot -Fe 3+ NC hydrogel displays extremely balanced and high mechanical properties (the fracture strain of 2663%, fracture stress of 4.00 MPa and toughness of 71.30 MJ/m 3 ), good self-recovery capacity (ca. 80.5% toughness recovery after 4 h of resting) and fatigue resistance. Basing on the dynamic and reversible nature of coordination bonds, the PAmAc-Cdot -Fe 3+ hydrogel also shows the stimulation-triggered shape memory performance. All the above results indicate that the introduction of strong coordinate bonds into NC hydrogel is a promising alternative method to fabricate dual cross-linked NC hydrogels with excellent comprehensive properties and functions, which have potential applications in load-bearing soft devices and soft actuators.